2012
DOI: 10.4067/s0718-221x2012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades físicas y mecánicas de compuestos de polietileno reciclado y harinas de corteza y madera de Pinus radiata fabricados mediante moldeo por inyección

Abstract: RESUMENSe ensayaron compuestos de polietileno de baja densidad reciclado y harina de madera y de corteza de Pinus radiata D. Don, para evaluar el efecto del contenido de harina y la densidad del compuesto sobre la absorción de agua e hinchamiento, dureza Rockwell, resistencia a la tracción y módulo de elasticidad en tracción. Estos compuestos fueron fabricados mediante moldeo por inyección y sin aditivos, en proporciones harina/polietileno de 20/80, 40/60 y 60/40 peso/peso. Se determinaron varias propiedades f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…In turn, these values are similar to those of most of the composites made with different virgin and recycled thermoplastics, with or without the use of chemical additives, by injection, compression or extrusion methods, which have been assessed by various researchers such as Bledzki and Faruk (2004), Yang et al (2006), Ngueho et al (2010), Zabihzadeh (2010) and Moya et al (2012).…”
Section: Tensile Strengthsupporting
confidence: 50%
See 4 more Smart Citations
“…In turn, these values are similar to those of most of the composites made with different virgin and recycled thermoplastics, with or without the use of chemical additives, by injection, compression or extrusion methods, which have been assessed by various researchers such as Bledzki and Faruk (2004), Yang et al (2006), Ngueho et al (2010), Zabihzadeh (2010) and Moya et al (2012).…”
Section: Tensile Strengthsupporting
confidence: 50%
“…The WP board had 4.13 % moisture; this content is given by the use of thermoplastic waste as raw material, which promotes resistance to water penetration and also allows good encapsulation between the particles of the wood used and the thermoplastic matrix, thus weakening the wood's hygroscopic capacity. These results are related to those obtained by Moya et al (2012), who determined that MC variation in WP boards depends on the sawdust content used, employing proportions of 20, 40 and 60 %. The comparisons showed that the best stability is between 40 and 60 % wood.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations